Wound healing activity of terpinolene and α-phellandrene by attenuating inflammation and oxidative stress in vitro. Issue 2 (May 2019) - de Christo Scherer, Marcella Malavazi; Marques, Franciane Martins; Figueira, Mariana Moreira; Peisino, Maria Carolina Oliveira; Schmitt, Elisângela Flávia Pimentel; Kondratyuk, Tamara P.; Endringer, Denise Coutinho; Scherer, Rodrigo; Fronza, Marcio
Abstract: This study was undertaken to investigate the in vitro wound healing effects and the anti-inflammatory and antioxidant activities of terpinolene and α-phellandrene. The in vitro stimulatory effects on the proliferation and migration of fibroblasts were assessed using the scratch assay. The anti-inflammatory activity was evaluated using cell-based assays by investigating their influence on nitric oxide (NO), superoxide anion (O2 - ), tumour necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) production and using the TNF-α-induced nuclear factor kappa (NF-κB) assay. Antioxidant activity was determined by the ABTS cation radical scavenging capacity, ferric reducing/antioxidant potential (FRAP), and NO free radical scavenging assays. Terpinolene and α-phellandrene significantly increased the migration and proliferation of fibroblasts and suppressed the pro-inflammatory cytokines IL-6 and TNF-α in a dose-dependent manner. Terpinolene and α-phellandrene at a concentration of 100 μM significantly inhibited NO production (41.3 and 63.8%, respectively) in a macrophage cell-culture-based assay, and resulted in reductions in O2 - production of 82.1 ± 3.5% and 70.6 ± 4.3%, respectively. Moreover, these monoterpenes were verified to suppress NF-κB activity. In summary, terpinolene and α-phellandrene may contribute to broadening clinical options in the treatment of wounds by attenuating inflammation and oxidative stress in vitro. Graphical abstract: Image 1 Highlights: Terpinolene and α-phellandrene were assayed for skin care applications. Both reduced the intracellular oxidative stress environment. They suppressed the overproduction of pro-inflammatory cytokines of IL-6 and TNF-α. Both contribute to wound re-epithelialization by stimulating fibroblast migration. Data elicited benefits for the treatment of skin lesions.